Advances in the application of named reactions in polymer synthesis. (June 2023) - Lu, Dawei; Zou, Xudong; Li, Chaofan
With the development of polymer science, more and more named reactions have been applied to synthesizing polymers. Introducing new reactions into polymer synthesis is undoubtedly an excellent expansion for monomer and polymer libraries. In this review, the named reactions employed in polymer-chain synthesis were divided into seven types: electrophilic reactions, nucleophilic reactions, transition metal-mediated cross-coupling reactions, free radical reactions, pericyclic reactions, multi-component reactions and rearrangement reactions. The discussion was mainly focused on the progress in the utilization of these named reactions in polymer synthesis, which could be a valuable reference for researchers in the polymer field.